Use of a non-medicated plaster in chronic lumbar back pain: a randomized controlled trial - Ricci, Matteo; Mulone, Alessio; Elena, Nicholas; Vecchini, Eugenio; Valentini, Roberto; Gelmini, Margherita (Acta Biomedica Atenei Parmensis, 2022)
BACKGROUND: The latest technology on far infrared radiations reflects the radiations emitted by the human body and induces an antalgic and anti-inflammatory effect without active ingredients. Our primary aim was to assess pain level modifications throughout the treatment period with two different types of patches, compared to a placebo. As secondary aims, we focused on addressing patients’ quality of life and range of motion changes with each patch. METHODS: We assessed 54 patients with chronic lumbar back pain treated with FIT Therapy (far infrared technology) patch. Three different types of FIT Therapy patches (F4, F3, and placebo) were used according to the different power of action and patients allocated in a randomized fashion into the 3 arms of the study. Every single patient was assessed during the study using the VAS pain scale, the Roland Morris Disability Questionnaire for quality of life, and ROM for a total of 14 days. RESULTS: Only the F4 patch group significantly reduced pain level at T14 compared to the placebo group (p<0.05). Meanwhile, F3 showed only a non-significant decrease compared to placebo (p=0.254). In terms of lifestyle improvements, both F3 and F4 recorded a decrease on the RMDQ of 4 and 6 points, respectively. CONCLUSIONS: Currently, we still need further studies with longer follow-up to consider the FIT Therapy patches F4 a valid alternative as a “non-medicated pain relief”, but it proved to have a role in alleviating painful symptoms and improving function in chronic lumbar back pain without adverse events.